Description of internet gaming disorder in students - Khairati, Annisaislami; Ifdil , Ifdil (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2024)
This research delves into a global phenomenon where rapid technological advancements have transformed the nature of adolescent games. Internet gaming disorder is a disorder experienced by individuals characterized by the inability to control the intensity of gaming in their daily lives. Adolescents often experience internet gaming disorder due to their preference for trying new things for personal pleasure. The type of research used in this research is quantitative with descriptive methods. The sample in this study was 286 students selected using simple random sampling techniques. Data were obtained by providing research instruments in the form of questionnaires to students. The results of the study show that the tendency of internet gaming disorder in students is generally in the low category, which means that many of the students are not indicated to have internet gaming disorder. It is influenced by environmental factors, that students who attend religious schools, make students aware of the negative impact of online gambling addiction, and also make students have high self-control so as not to become addicted to playing online games.